SPELEOTHEM LUMINESCENCE INTENSITY AND SPECTRAL CHARACTERISTICS: SIGNAL CALIBRATION AND A RECORD OF PALAEOVEGETATION CHANGE - Baker A.; Barnes W.L.; Smart P.L. (My University, 1996)
The intensity and spectral characteristics of speleothem luminescence are investigated for signs of any potential palaeoenvironmental signals. Luminescence in speleothems has been demonstrated to have an organic acid source, acids being transported from the overlying soil to the speleothem via the groundwater system. Luminescence spectral characteristics confirm a humic/fulvic acid source of the luminescence, but are unable to distinguish between plant acids derived from different vegetation systems. Spectral characteristics also differ between solid and dissolved speleothem calcite. The influence of six factors on luminescence intensity are considered; changes in organic acid concentration, organic acid structural type, depth of the sample below the surface, dilution effects through changes in water discharge rate, dilution effects through changes in speleothem growth rate, and the effects of luminescence quenching due to the presence of metal ions. In a Holocene stalagmite sample from Sutherland a period of low luminescence intensity is observed, which is demonstrated to correlate with periods of blanket bog expansion recorded in the regional pollen record. This suggestion is supported by a study of 18 recently deposited samples from Northwest Europe and 5 cave water samples feeding stalagmites in a British cave, where a relationship to vegetation is evident, with very low luminescence intensity observed from sites overlain by blanket bog deposits. This is thought to be due to both low organic acid concentrations in feedwaters, and also the low luminescence efficiency of the humic acids from bog sites due to their structural characteristics.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен